Oxygen deficiency introduced to Z-scheme CdS/WO3−x nanomaterials with MoS2 as the cocatalyst towards enhancing visible-light-driven hydrogen evolution. Issue 22 (29th May 2019) - Li, Fengyuan; Hou, Yanping; Yu, Zebin; Qian, Lun; Sun, Lei; Huang, Jun; Ran, Qi; Jiang, Ronghua; Sun, Qianqian; Zhang, Heqing
Abstract : Oxygen deficiency modified Z -scheme CdS/WO3− x nanomaterials with MoS2 as the cocatalyst showed excellent photocatalytic behavior and photostability. Abstract : An oxygen deficiency modified Z -scheme CdS/WO3− x nanohybrid with MoS2 as the cocatalyst was synthesized by a microwave hydrothermal method and was used for photocatalytic hydrogen production under visible light irradiation. Loadings of WO3− x and MoS2 as well as the synthesis time of the microwave-assisted hydrothermal process were optimized, and the physicochemical and optical properties of the as-prepared photocatalysts were characterized by various techniques. Results showed that the material with 30 wt% of WO3− x, 0.1 wt% of MoS2 and a preparation time of 120 minutes exhibited the most desirable morphology and structure for hydrogen production. The maximum hydrogen production of 2852.5 μmol g −1 h −1 was achieved, which was 5.5 times that of pure CdS (519.1 μmol g −1 h −1 ) and 1.5 times that of CdS/30 wt% WO3− x (1879.0 μmol g −1 h −1 ), and the external quantum efficiency (EQE) reached 10.0% at 420 nm. The improvement of photocatalytic performance could be attributed to the Z -scheme formed between CdS and WO3− x and MoS2 as an electron trap. It is worth mentioning that the size of the composite had a negative correlation with the H2 production rate.